EKUMENISME BERDASARKAN MEISTER ECKHART DAN IBN AL-ARABI YANG DIKEMBANGKAN DARI WHEN MYSTIC MASTERS MEET - Yan Okhtavianus Kalampung (Jurnal Orientasi Baru, 2015)
Ecumenism as a movement always pursue movement that always include as many as possible people in this world. To make that real, the thought of Meister Eckhart and Ibn Al-Arabi can be a great inspiration. In this paper i argue that Eckhart and Arabis thought about Cosmic Spirituality can contribute to Participative Ecumenism especially in Asia with all the context in it. Their concept with stresses in relation of all Creation in this world can make something in the struggle of Asian People. The relation of all Creation can make support the Ecumenism with a great care of Poverty and real engagement in Interreligious Dialogue.